The Role of Non-Human Sialic Acid Neu5Gc-Containing Glycoconjugates in Human Tumors: A Review of Clinical and Experimental Evidence - Rancés Blanco; Juan P. Muñoz (Biomolecules)
N-Glycolylneuraminic acid (Neu5Gc) is a sialic acid variant commonly found in most mammals but not synthesized by humans due to an inactivating mutation in the CMP-Neu5Ac hydroxylase (CMAH) gene. Despite this, Neu5Gc-containing molecules are consistently detected in human tissues, particularly in malignant tumors. However, the mechanisms underlying Neu5Gc accumulation and its role in cancer development remain poorly understood. Objectives: This review aims to analyze clinical and experimental evidence regarding the presence of Neu5Gc-containing glycoconjugates in both tumor and non-tumor human tissues, exploring potential mechanisms of the Neu5Gc expression and evaluating its contribution to tumor biology, with a particular focus on the Neu5Gc-GM3 ganglioside. Methods: A comprehensive review of the literature was conducted, integrating findings from immunohistochemistry, chromatography, and molecular studies to assess the expression and implications of Neu5Gc in cancer biology. Results: Neu5Gc-containing glycoconjugates were found to preferentially accumulate in various malignant tumors, while their presence in normal tissues was restricted to cells with high turnover rates. This accumulation is potentially mediated by dietary uptake, hypoxic conditions, and metabolic alterations in cancer cells. Additionally, Neu5Gc-containing molecules were associated with the activation of oncogenic pathways. Conclusion: Neu5Gc-containing glycoconjugates play a multifaceted role in cancer progression and present potential as prognostic markers and therapeutic targets.